2020
DOI: 10.1177/2325967120919178
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Based Differences in Anterior Cruciate Ligament Injuries Among United States High School Soccer Players: An Epidemiological Study

Abstract: Background: Anterior cruciate ligament (ACL) tears are common among high school athletes, with sex-based differences accounting for higher injury rates in girls. Previous epidemiological studies on ACL injuries focusing on adolescent athletes have looked at injuries across multiple sports, but few have analyzed ACL tears in solely high school soccer athletes. Purpose: To examine sex-based differences in the epidemiology of ACL injuries among high school soccer players in the United States (US). Study Design: D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 18 publications
1
17
0
5
Order By: Relevance
“…After sub-grouping by age group and sex, this proportion was 60% in adult female athletes (95% CI 49–70, I 2 = 85%) and 52% in adult male athletes (95% CI 43–60, I 2 = 86%) (Appendix A5-2). There were insufficient studies to investigate injury proportions by sex in adolescents (Appendix A5-3) [ 53 , 59 , 66 ]. None of the included studies investigated children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After sub-grouping by age group and sex, this proportion was 60% in adult female athletes (95% CI 49–70, I 2 = 85%) and 52% in adult male athletes (95% CI 43–60, I 2 = 86%) (Appendix A5-2). There were insufficient studies to investigate injury proportions by sex in adolescents (Appendix A5-3) [ 53 , 59 , 66 ]. None of the included studies investigated children.…”
Section: Resultsmentioning
confidence: 99%
“…After sub-grouping by exposure types and sex, injury incidence in female athletes during competition was 0.67 per 1000 player-hours (95% CI 0.33–1.35, I 2 = 75%) and in training was 0.07 per 1000 player-hours (95% CI 0.05–0.10, I 2 = 2%) (Appendix A11-3). There were insufficient studies to perform meta-analysis by player-exposures in females [ 45 , 53 ]. For males, injury incidence was 0.37 per 1000 player-hours (95% CI 0.24–0.59, I 2 = 72%) and 0.34 per 1000 player-exposures, 95% CI 0.12–0.99, I 2 = 96%) during competition while for training was 0.02 per 1000 player-hours (95% CI 0.01–0.05, I 2 = 55%) and 0.03 per 1000 player-exposures (95% CI 0.01–0.06, I 2 = 83%).…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first study to use GPS-derived external workload metrics to evaluate lower extremity injury risk in women’s soccer. Studies comparing men’s and women’s soccer have demonstrated that men are more likely to sustain groin and hamstring injuries, 10 , 54 whereas women have a higher risk of anterior cruciate ligament (ACL) tears, 28 , 33 ankle ligament injuries, 35 and concussions. 14 Furthermore, consistent with previous findings, 17 , 26 the present study found that the incidence of lower extremity injury was over 3 times higher in games than in practices, at rates of 11.25 injuries per 1000 game hours and 3.07 injuries per 1000 practice hours, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We expect injuries still occurred as COVID-precautions varied regionally and a portion of athletes continued to practice and play informally. Per Gupta et al 15 , rates of ACL injury are significantly lower in practice versus competition, therefore the decrease in scheduled competitions alone may have led to fewer injuries. There are some studies suggesting that the rate of sports injuries O n l i n e F i r s t increases at the beginning of a sports season.…”
Section: Discussionmentioning
confidence: 99%